2021
DOI: 10.1364/oe.424336
|View full text |Cite
|
Sign up to set email alerts
|

Single-frequency 1.7-μm Tm-doped fiber laser with optical bistability of both power and longitudinal mode behavior

Abstract: The single-frequency operation of a thulium fiber laser at a short wavelength of 1720 nm is investigated in a ring resonator. Powerful single-longitudinal-mode operation was realized by utilizing an unpumped thulium-doped fiber as the saturable absorber. The fiber laser delivered 407 mW single-frequency output with a spectral linewidth of 4.4 kHz under 2.7-W launched pump power at 1570 nm, which turned to multi-longitudinal-mode operation at higher pump powers. Additionally, optical bistability of both output … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Therefore, we used a 20% pilot overhead in the carrier recovery to remove the cycle slips. The pilot overhead could be significantly reduced if a carrier recovery algorithm with high tolerance to phase noise is used 38 , 39 or a narrow-linewidth laser is utilized for the 1.74-μm-band pump 40 . We have investigated the use of low-density parity-check (LDPC) code overheads of 20%, 25% and 33%.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we used a 20% pilot overhead in the carrier recovery to remove the cycle slips. The pilot overhead could be significantly reduced if a carrier recovery algorithm with high tolerance to phase noise is used 38 , 39 or a narrow-linewidth laser is utilized for the 1.74-μm-band pump 40 . We have investigated the use of low-density parity-check (LDPC) code overheads of 20%, 25% and 33%.…”
Section: Resultsmentioning
confidence: 99%
“…Another frequency selection method in ring cavity is using rare earth ions-doped fiber as saturable absorber, which is simple, robust and can effectively suppress the mode instability. By using the Tm 3+ -doped fiber as the saturable absorber, our team has demonstrated a 1720 nm single-frequency fiber ring laser with a maximum single-frequency output power of 400 mW [57]. The power scaling was limited by the high laser threshold, which is resulted from the strong absorption of Tm 3+ -doped fiber at 1.7 μm.…”
Section: Wavelength Extensionmentioning
confidence: 99%
“…[ 23 ] In our previous work, unpumped thulium‐doped fibers have been used as SAs to achieve SLM operation at 1720 nm. [ 24 ] In that work, we found that the oscillator exhibited strong optical bistability and the laser threshold changed significantly with the SA fiber length. Indeed, in the case where the SA fiber length was 0.75 m, the laser threshold exceeded 6 W and the laser output was the multilongitudinal mode (MLM).…”
Section: Introductionmentioning
confidence: 96%